Oxygen-dependence of upper thermal limits in crustaceans from different thermal habitats. (October 2020) - Ern, Rasmus; Chung, Dillon; Frieder, Christina A.; Madsen, Niels; Speers-Roesch, Ben
Abstract: The critical thermal maximum (CTMAX ) is the temperature at which animals exhibit loss of motor response because of a temperature-induced collapse of vital physiological systems. A central mechanism hypothesised to underlie the CTMAX of water-breathing ectotherms is insufficient tissue oxygen supply for vital maintenance functions because of a temperature-induced collapse of the cardiorespiratory system. The CTMAX of species conforming to this hypothesis should decrease with declining water oxygen tension (PO2 ) because they have oxygen-dependent upper thermal limits. However, recent studies have identified a number of fishes and crustaceans with oxygen-independent upper thermal limits, their CTMAX unchanged in progressive aquatic hypoxia. The previous studies, which were performed separately on cold-water, temperate and tropical species, suggest the oxygen-dependence of upper thermal limits and the acute thermal sensitivity of the cardiorespiratory system increases with decreasing habitat temperature. Here we directly test this hypothesis by assessing the oxygen-dependence of CTMAX in the polar Antarctic krill ( Euphausia superba ), as well as the temperate Baltic prawn ( Palaemon adspersus ) and brown shrimp ( Crangon crangon ). We found that P. adspersus and C. crangon maintain CTMAX in progressive hypoxia down to 40 mmHg, and that only E. superba have oxygen-dependent upper thermal limits at normoxia. In E. superba, the observed decline in CTMAX with water PO2 is further supported by heart-rate measurements showing a plateauing, and subsequent decline and collapse of heart performance at CTMAX . Our results support the hypothesis that the oxygen-dependence of upper thermal limits in water-breathing ectotherms and the acute thermal sensitivity of their cardiorespiratory system increases with decreasing habitat temperature. Highlights: Critical thermal maximum of Antarctic krill decreases with water oxygen tension. Critical thermal maximum of krill is caused by insufficient oxygen supply capacity. Temperate crustaceans maintain critical thermal maximum in moderate hypoxia. Acute cardiorespiratory thermal tolerance decreases with habitat temperature.